PENGARUH PEMANTAUAN DAN PEMBINAAN ZAKAT PRODUKTIF TERHADAP PEMBERDAYAAN MUSTAHIK DI POS KEADILAN PEDULI UMMAT ACEH - Hamdani, Hamdani (JURNAL KEBANGSAAN, 2019)
This study aimed to explore the influence of monitoring and coaching to empower productive zakat mustahik at Pos Keadilan Peduli Ummat (PKPU) Aceh. Primary data were obtained by questionnaire and interview. The researcher spread questionnaire to the mustahik and interview them during filling questionnaire. The population of this research are 496 mustahik and the sample of this research are 100 mustahik. Technique sampling of this research used Proportionate Stratified Random Sampling. The researcher used qualitative approach by using exploratory research and descriptive analysis. The results of this research is unsalted feed, it could be seen from their answer, most of them doubt on answering the questionnaire. However, to be careful in trying to answer mustahik agreed by 34%. The mustahik are very careful in using zakat were mandated to them as mustahik. Mean while, the effect of coaching productive zakat to empowerment was not significant, it appears that most of them answered doubt. Were as, the comparison of income before and after monitoring and coaching, the changing was great and if it could be maintained, the amount of the average income is Rp. 2,859,500,- thus the changing of family economic it would be prosperous family.Keywords: Monitoring, Coaching, Productive Zakat, Mustahik Empowerment